Valuing urban accessibility and air quality in Sweden: A regional welfare analysis - Chuan-Zhong Li; Gunnar Isacsson (Uppsala University, Department of Economics, 2009)
This paper is concerned with the implicit values of urban accessibility and air quality in Sweden. Based on the hedonic wage and rent theory, we construct an econometric model to compute such values, and illustrate their implications for regional sustainability analysis. It is shown that for most Swedish cities, welfare has increased from 1986 to 1998 due to improved air quality but the positive effect is partly offset by the deteriorated accessibility in some areas. The results also indicate that the values people place on urban accessibility and air quality vary considerably across regions.
urn:nbn:se:uu:diva-100815
Keywords: D6; R10; Q51; 330; hedonic pricing; air quality; urban accessibility; welfare analysis; Luftreinhaltung; Luftverschmutzung; Hedonischer Preisindex; Wohlfahrtsanalyse; Schweden